Determining the Optimum Location for Charging Stations Based on Voltage Stability in the Microgrid - Ngoc Thuong Huynh Thi; Trieu Tan Phung; Trong Nghia Le; Huy Anh Quyen; Duy Anh Ta; Tung Giang Tran (Journal of Technical Education Science, 2025)
The paper presents the investigation into determining suitable locations for electric vehicle charging stations within the Microgrid 16-Bus system based on the objective of considering voltage stability using the FVSI and RVS indices. This study examines the impact of charging stations on the electrical grid at each bus during charging power mode by evaluating the FVSI and RVS parameters of the Microgrid when varying charging power respectively at each bus. Consequently, this research draws conclusions regarding optimal charging station placements or recommendations for locations where charging stations should not be placed. Simulation results demonstrate the effectiveness of voltage stability indices in identifying nodes with significant voltage loss. Hence, identifying buses to avoid installing charging stations and determining stable buses where charging stations can be installed. Specifically, the system frequency only recovers with charging levels below 50%. Bus 5 is identified as advantageous in terms of voltage, with the lowest FVSI of 0.185 among load buses. The simulation process and testing the effectiveness of the proposed method are evaluated using PowerWorld software. Simulation results demonstrate that the proposed locations provide voltage stability. The voltage drop at Bus 5 is only 1.52%, which is 5% lower than the normal allowable value of national power grids.